2018
DOI: 10.1002/2017gb005644
|View full text |Cite
|
Sign up to set email alerts
|

The Temperature Sensitivity (Q10) of Soil Respiration: Controlling Factors and Spatial Prediction at Regional Scale Based on Environmental Soil Classes

Abstract: The temperature sensitivity of heterotrophic soil respiration is crucial for modeling carbon dynamics but it is variable. Presently, however, most models employ a fixed value of 1.5 or 2.0 for the increase of soil respiration per 10°C increase in temperature (Q10). Here we identified the variability of Q10 at a regional scale (Rur catchment, Germany/Belgium/Netherlands). We divided the study catchment into environmental soil classes (ESCs), which we define as unique combinations of land use, aggregated soil gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
107
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(117 citation statements)
references
References 71 publications
10
107
0
Order By: Relevance
“…A clear picture presented that labile SOC is less sensitive to warming than recalcitrant SOC by using three methods (Figure ). Our findings were in line with the CQT hypothesis that recalcitrant SOC is more sensitive to warming than labile SOC, which was supported by some individual studies (e.g., Leifeld & Fuhrer, ; Conant et al, ; Craine et al, ; Lefèvre et al, ; Meyer et al, ). Although the kinetic theory underlying the CQT hypothesis (Davidson & Janssens, ), it is well applied only if SOC recalcitrance solely determines decomposition rates.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A clear picture presented that labile SOC is less sensitive to warming than recalcitrant SOC by using three methods (Figure ). Our findings were in line with the CQT hypothesis that recalcitrant SOC is more sensitive to warming than labile SOC, which was supported by some individual studies (e.g., Leifeld & Fuhrer, ; Conant et al, ; Craine et al, ; Lefèvre et al, ; Meyer et al, ). Although the kinetic theory underlying the CQT hypothesis (Davidson & Janssens, ), it is well applied only if SOC recalcitrance solely determines decomposition rates.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, apparent increases in soil C availability at high temperature (Kadlec & Reddy, ) may intensify microbial nutrient limitation. In comparison with previous individual studies (Balogh et al, ; Meyer et al, ; Zheng et al, ), our work obtained a broad range of SOC concentration (0.5–551.6 g/kg), which may enable us to observe this threshold. Therefore, we can also assume that the various ranges of SOC contents in individual studies may cause the different correlations between Q 10 and SOC content.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the compost treatments, the lowest Q 10 value of Rh was present in BPFS. The Q 10 of Rh may not altered by the organic C quantity as observed here and by Meyer et al () but depend on C quality, with positive, negative, and nonsignificant relationships all being reported in the literature (Karhu et al, ). We found that the Q 10 of Rh increased with decreasing carbohydrates, proteins, and phenolic C, and increasing V/VSC (Figure ).…”
Section: Discussionsupporting
confidence: 78%
“…where ST is the soil temperature, Rs is the soil respiration rate at the given soil temperature, and a and b are fitted parameters. Then, the temperature sensitivity (Q10) values were calculated by inserting the parameter b [37]:…”
Section: Resultsmentioning
confidence: 99%